Peningkatan Kewaspadaan Dini terhadap Anemia pada Lansia melalui Pemeriksaan Hemoglobin dan Golongan Darah - Gela Setya Ayu Putri; Meutya Fajri Halmi; Chandra Eko Ardianto (Universitas Muhammadiyah Semarang, 2025)
Anemia is still a worldwide health issue. The high prevalence of anemia necessitates special attention because anemia can trigger a variety of health problems in the elderly. The goal of this community service is to perform hemoglobin and blood type tests on elderly residents of Tambak Bulusan village in Demak to early detection of anemia and raise awareness about anemia in the elderly. Community service activities were conducted in Tambak Bulusan Village, Karangtengah, Demak Regency, Central Java. There are three steps involved: preparation, implementation, and evaluation. The hemoglobin test is performed using a POCT device, and the blood group test is performed manually. The community service was attended by 32 elderly people. The percentage of correct answers on the pre-test and post-test was 39.7% and 71.3%, respectively. There was a difference in the level of residents knowledge before and after education (p<0.05) with an increase in knowledge of 31.6%. The hemoglobin (Hb) level test showed an average of 11.9 ± 1.3 g/dL, with 21 residents (66%) having Hb levels below normal, 10 residents (31%) having normal Hb levels, and 1 resident (3%) having Hb levels above normal. Blood type test found all blood types, namely A, B, O, and AB rhesus positive with a dominance of blood type O. The conclusion after the community service activities, the knowledge of elderly residents increased by 31.6%. A total of 21 residents (66%) had hemoglobin levels below normal or showed signs of anemia. All types of blood types were found with a dominance of blood type O. All residents have positive rhesus.